2022
DOI: 10.1155/2022/4237633
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed Genes Associated with the Prognosis and Diagnosis of Hepatocellular Carcinoma by Integrated Bioinformatics Analysis

Abstract: Objective. The goal of this study was to understand the possible core genes associated with hepatocellular carcinoma (HCC) pathogenesis and prognosis. Methods. GEO contains datasets of gene expression, miRNA, and methylation patterns of diseased and healthy/control patients. The GSE62232 dataset was selected by employing the server Gene Expression Omnibus. A total of 91 samples were collected, including 81 HCC and 10 healthy samples as control. GSE62232 was analysed through GEO2R, and Functional Enrichment Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The study emphasizes techniques including surgical resection, biannual ultrasonography surveillance, and liver transplantation for cirrhotic patients, acknowledging the therapeutic importance of these findings within the larger framework of liver cancer research. The necessity for continuous research to improve clinical procedures and the management of HCC is highlighted by common methods such as image-guided ablation, chemoembolization, and systemic therapy [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study emphasizes techniques including surgical resection, biannual ultrasonography surveillance, and liver transplantation for cirrhotic patients, acknowledging the therapeutic importance of these findings within the larger framework of liver cancer research. The necessity for continuous research to improve clinical procedures and the management of HCC is highlighted by common methods such as image-guided ablation, chemoembolization, and systemic therapy [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings provide insights into the potential roles of these key genes in immune invasion in liver cancer. (45)(46)(47). Nucleolar and spindle-associated protein 1 (NUSAP1) is a member of the NUSP1 family of nucleolar-spindle-associated proteins and is involved in spindle microtubule organization (48).…”
Section: Discussionmentioning
confidence: 99%
“…To further confirm and evaluate potential therapeutic values from the novel identified up-regulated DEGs with the impacts of decreased survival in the current study, we chose to validate genes that were the top ten up-regulated DEGs with decreased survival and not shown to be associated with tumorigenesis. Among them, studies have proved that CCNB1, RACGAP1 and NUSAP1 promote the progression of multiple cancers (Aljohani et al 2022;Gu et al 2022;Guo et al 2020), and NCAPG and CCNB2 have been found to be associated with a poor prognosis of ES (Kakar et al 2022;Zhao et al 2022), while ASPM, CENPF, CKS2, and DTL have not been studied in ES to the best of our knowledge. Interestingly, these four genes were also found in the GO analysis and GSEA results (Fig.…”
Section: In Vitro Verification Of Four Up-regulated Degs With Decreas...mentioning
confidence: 98%